Enhancing Readiness of Islamic Education Teachers in Implementing Scientific Learning and Authentic Assessment - Suparjo (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
This study examines the acceptance and readiness of PAI (Islamic Education) teachers towards the implementation of Curriculum 2013. The objective is to assess their acceptance of the curriculum, readiness to implement the scientific approach and authentic assessment, and their paradigm shift in education. Surveys were conducted to collect data, which was analyzed using mean scores. The findings reveal that PAI teachers in primary schools and Islamic schools have a positive attitude towards Curriculum 2013 and are ready to implement it. They also demonstrate an understanding of the scientific approach and authentic assessment. The results indicate the dedication and adaptability of PAI teachers in meeting the changing demands of education. Their paradigm shift aligns with the goals of Curriculum 2013, highlighting their commitment to delivering high-quality Islamic education. These findings have important implications for educational stakeholders in supporting and empowering PAI teachers, emphasizing the need for continuous professional development. Overall, the study showcases the positive disposition and preparedness of PAI teachers in embracing the changes brought by Curriculum 2013, ensuring effective teaching and learning experiences for students.